A 1550 nm All-Optical VCSEL-to-VCSEL Wavelength Conversion of a 8.5 Gb/s Data Signal and Transmission over a 24.7 km Fibre - Boiyo, Kiboi; Isoe, G. M.; Gamatham, R.R.G.; Leitch, A.W.R.; Gibbon, T.B. (International Society for Optics and Photonics, 2017)
For the first time, we demonstrate, VCSEL-to-VCSEL wavelength conversion within the low attenuation 1550 nm transmission window, including transmission over fibre and bit error rate (BER) performance characterization. We experimentally demonstrate a low injection power optical wavelength conversion by injecting an optical beam from a signal carrier master vertical cavity surface-emitting laser (VCSEL) into the side-mode of the slave VCSEL. This technique solves the challenge of wavelength collisions and also provides wavelength re-use in typical wavelength division multiplexed (WDM) systems. This paper, for the first time, uses two 1550 nm VCSELs with tuneability range of 3 nm for a 5-9.8 mA bias current. The master VCSEL is modulated with a non-return-to-zero (NRZ) pseudo-random binary sequence (PRBS_27 -1) 8.5 Gb/s data. A data signal conversion penalty of 1.1 dB is realized when a 15 dBm injection beam is used. The transmission performance of the converted wavelength from the slave VCSEL is evaluated using BER measurements at a 10-9 threshold level. A 0.5 dB transmission penalty of the converted wavelength data is realized in an 8.5 Gb/s transmission over 24.7 km. This work is vital for optical fibre systems that may require wavelength switching for transmission of data signals.
Keywords: VCSELs; Wavelength Conversion; Data signals; Fibre links